(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
Accidental release of biohydrogen (bioH2) gas in biogas plant has a high risk to cause fire and explosion incidents. Thus, computational fluid dynamics (CFD) was used to study the dispersion of 158 kg of bioH2 gas through pipe leaks at a pure bioH2 spherical storage tank. The TNT-equivalent explosion model found that the threat zone which can destroy buildings due to overpressure exceeding 55 kPa was located at a radius of 9.31 m from the centre of the explosion at the fermenter. Further evaluation using the Dow’s fire and explosion index (F&EI) expects a maximum probable day outage (MPDO) and business interruption (BI) of 43 days and USD165,210, respectively. Therefore, safety control in terms of elimination of ignition sources, material replacement, engineering controls, safety components, layout design, administrative controls and personal protective equipment have been successfully proposed. In conclusion, this study has successfully simulated the dispersion of bioH2 gas and evaluated the impact of fire and explosion on biogas plant.